أثر التسويق الرقمي على نمو المؤسسات الناشئة دراسة ميدانية على عينة من المؤسسات الناشئة بالجزائر - بن طالب سناء; خرخاش نادية; رجم خالد (جامعة الوادي University of Eloued, 2024)
The study aimed to elucidate the impact of digital marketing on achieving the growth of startups, To accomplish the study, we relied on an electronic questionnaire distributed to 40 startups from various states in Algeria, 36 usable questionnaires were retrieved and processed using the (SPSS v26),The study found a significant and statistically meaningful impact between the two variables, with a strong correlation too, This emphasizes the importance of adopting digital marketing within the startups companies, the study recommends the necessity of utilizing modern technologies in this field to ensure the achievement of a strong competitive position.
The impact of digital marketing on start-ups growth Field study on a sample of startups in Algeria
Keywords: تسويق رقمي; مؤسسات ناشئة; نمو; ميزة تنافسية; Digital marketing; startups; Growth; Competitive advantage